PENGEMBANGAN APLIKASI AUGMENTED REALITY UNTUK PEMBELAJARAN BIOLOGI MENGGUNAKAN MARKER BASED TRACKING PADA PLATFORM ANDROID - Teguh Brahmana; Taufiq; Rizki Suwanda (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The development of Augmented Reality (AR) technology offers significant opportunities for creating interactive learning media, especially for abstract Biology topics. This study aims to develop an AR-based learning application using the marker-based tracking method on the Android platform. The developed application, named BioAR, presents a three-dimensional model of animal cell structures that can be displayed through the device’s camera with the help of markers. The development method used in this application is the Waterfall model, which consists of several stages: literature review, data collection, system design, application development, and testing. The 3D models of the organelles are created using Blender, then integrated into Unity with the use of Vuforia SDK. The application is tested using the black-box testing method, focusing on the functionality of navigation buttons, the distance between the camera and marker, light intensity, marker type, and testing on various Android devices with different specifications. The testing results show that the application performs well according to the designed functions. The application successfully displays 3D objects in real-time at an ideal distance between the camera and marker, ranging from 20–30 cm, with adequate lighting. Devices with at least 3 GB of RAM and high-quality cameras provide optimal results. This application is expected to serve as an alternative interactive learning media, easily accessible, and help visualize Biology material in a more engaging way.